The EMG, NIRS, and RPE responses to two turn transition techniques in alpine skiing - John G. Seifert; Ronald W. Kipp; Shannon Griffin; David Graham (Elsevier, 2023)
Summary: Objective: Two techniques facilitate the transition in an alpine ski turn, extension (EXT) and flexion (FLEX). The purpose of this study is to compare NIRS, EMG, and RPE responses between EXT and FLEX in expert level skiers. Design: 24 Professional Ski Instructors of America Level III alpine ski instructors, examiners, and National Demonstration Team members completed one standardized run each of EXT and FLEX. A turn cycle, made of a right and left turn, was divided into four Phases. Methods: NIRS assessed HbO2 desaturation in the rectus femoris (RF) and vastus lateralis (VL). EMG was collected from the RF, VL, and gluteus medius (GM). Rating of Perceived Exertion (RPE, 0-10) assessed subjective exertion. Results: FLEX resulted in greater HbO2 desaturation in RF (−77.9 ​± ​21% vs. −67.5 ​± ​23%, p ​< ​0.001), VL (−69.8 ​± ​23.1% vs. −61.1 ​± ​24.6%, p ​< ​0.001) and RPE (6.0 ​± ​2.3 vs. 5.2 ​± ​2.0, p ​< ​0.001) compared to EXT. FLEX generally resulted in greater EMG activity in the steering and transition phases for RF and VL (p ​< ​0.001) while EXT resulted in greater activity GM on the inside leg. Conclusions: Caution should be exercised with recreational skiers as the FLEX transition resulted in significantly greater physiological stress compared to EXT. Localized hypoxia appears to be the focal point of this stress as HbO2 desaturation was ∼15% greater along with 15% greater RPE during FLEX. FLEX also produced greater EMG activity than EXT in the majority of the turn phases.